# From Newtonian systems to Lagrange mechanics using Euler - Lagrange equations [closed]

I am reading some notions about Lagrangian Mechanics from Holm's book.(page 12).

There is:

Every Newtonian system, $$m_i \ddot{q_i}=\frac{\partial V}{\partial q_i}, \mbox{ } i=\overline{1,N},$$ is equivalent to the Euler _ Lagrange equations,

$$\frac{d}{dt}\left(\frac{\partial L}{\partial \dot q}\right)-\frac{\partial L}{\partial q}=0,$$

for the Lagrangian $L$ defined by:

$$L(q, \dot{q})=\sum^{N}_{i=1}{\frac{1}{2}m_{i}\|\dot{q_{i}}\|^{2}}-V(q).$$

Proof For $L$ defined in the theorem,

$$\frac{d}{dt}\left(\frac{\partial L}{\partial \dot{q_{i}}}\right)-\frac{\partial L}{\partial q_{i}}=\ldots$$

I don't know how to derive:

$$\frac{d}{dt}\left(\frac{\partial L}{\partial \dot{q_{i}}}\right)$$

What I've tried:

$$\frac{d}{dt}{v(q)}=0$$ so I have to compute only $$\frac{d}{dt}\left(\frac{\partial L}{\partial \dot{q_{i}}}\right)$$

First of all I must to compute:

$$\frac{\partial L}{\partial \dot q_{i}}=\frac{1}{2}m_{i}\frac{\partial}{\partial \dot{q_i}}\|\dot q_{i}\|^2$$ So I have to compute the derivative for a dot product

So:

$$\frac{\partial}{\partial}\|\dot{q_i}\|^2=\frac{\partial}{\partial \dot {q_i}}\langle\dot{q_i},\dot{q_i}\rangle=\langle 1, \dot{q_i} \rangle + \langle \dot{q_i}, 1 \rangle$$

From here I got stuck... It is ok what I have done?

## closed as off-topic by ACuriousMind♦, Kyle Kanos, Martin, yuggib, Sebastian RieseSep 14 '15 at 13:30

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "Homework-like questions should ask about a specific physics concept and show some effort to work through the problem. We want our questions to be useful to the broader community, and to future users. See our meta site for more guidance on how to edit your question to make it better" – ACuriousMind, Kyle Kanos, Martin, yuggib
If this question can be reworded to fit the rules in the help center, please edit the question.

• Comment to the title (v2): To derive Lagrangian mechanics from Newtonian mechanics, we are supposed to derive EL equations (as opposed to assuming or using them). Did you mean the opposite way: From Lagrangian mechanics to Newtonian mechanics using EL equations? – Qmechanic Sep 13 '15 at 11:39
• Crossposted to math.stackexchange.com/q/1433397/11127 – Qmechanic Sep 13 '15 at 17:21

If I understood well, you want to find the second law of Newton using the Lagrangian and the Euler-Lagrange equation?

To make it easy, I'll only take one direction "$x$". Even if you can work with more degrees of freedom, it's the same application of Euler-Lagrange equation, so like that the writing will be lighter.

So you have the Lagrangian $$L_{x}=\frac{1}{2}m\dot{x}^{2}-V(x)$$ and the EL equation : $$\frac{d}{dt}(\frac{\partial L}{\partial \dot{x}})=\frac{\partial L}{\partial x}$$

Now you just apply the EL to the Lagrangian, so :

$$\frac{d}{dt}(\frac{\partial L}{\partial \dot{x}})=\frac{d}{dt}(m\dot{x})=m\ddot{x}$$

And

$$\frac{\partial L}{\partial x}= -\frac{\partial{V}}{\partial x}=F_{x}$$

If the force is conservative and derive from a potential energy :

$$F_{x}= -grad(V(x))$$

So we find :

$$m\ddot{x}=F_{x}$$

Second law of Newton. Like the EL works regardless of the coordinate system, we put "$q$" for expressed a general coordinate. Hope it was what you were looking for!

Given the Lagrangian $L(q, \dot{q})=\sum^{N}_{j=1}{\frac{1}{2}m_{j}\dot{q_{j}}^{2}}-V(q)$, $$\frac{\partial L}{\partial \dot q_{i}} =\sum^{N}_{j=1}{\frac{1}{2}m_{j}\frac{\partial (\dot{q_{j}}^{2})}{\partial \dot q_{i}}} = \sum^{N}_{j=1}{\frac{1}{2}m_{j} 2 \dot{q}_{j}\delta_{ij}} = m_i\dot{q}_i.$$

I guess you are stuck because of the dot product, but the index $i$ is not for the particle, but for a single degree of freedom, i.e. if you have one particle in a 3D space, your index is $i=1, 2, 3$, whilst with $N$ particles $i=1,2, \dots ,3N$.

In the case $\dot{q}_i = v_i$, your kinetic energy for one particle is $$T = \frac{1}{2}m (v_x^2+v_y^2+v_z^2),$$ for $N$ particles $$T =\sum_{i=1}^N \frac{1}{2}m_i (v_{ix}^2+v_{iy}^2+v_{iz}^2) = \sum_{j=1}^{N'}\frac{1}{2}m_j v_j^2$$ where $N'=3N$ and $j$ is the new index.